Targeted lung cancer therapy: preparation and optimization of transferrin-decorated nanostructured lipid carriers as novel nanomedicine for co-delivery of anticancer drugs and DNA - Shao, Zhenyu (Int J Nanomedicine, 2015)
PURPOSE: Nanostructured lipid carriers (NLC) represent an improved generation of lipid nanoparticles. They have specific nanostructures to accommodate drugs/genes, and thus achieve higher loading capacity. The aim of this study was to develop transferrin (Tf)-decorated NLC as multifunctional nanomedicine for co-delivery of paclitaxel (PTX) and enhanced green fluorescence protein plasmid. METHODS: Firstly, Tf-conjugated ligands were synthesized. Secondly, PTX- and DNA-loaded NLC (PTX-DNA-NLC) was prepared. Finally, Tf-containing ligands were used for the surface decoration of NLC. Their average size, zeta potential, drug, and gene loading were evaluated. Human non-small cell lung carcinoma cell line (NCl-H460 cells) was used for the testing of in vitro transfection efficiency, and in vivo transfection efficiency of NLC was evaluated on mice bearing NCl-H460 cells. RESULTS: Tf-decorated PTX and DNA co-encapsulated NLC (Tf-PTX-DNA-NLC) were nano-sized particles with positive zeta potential. Tf-PTX-DNA-NLC displayed low cytotoxicity, high gene transfection efficiency, and enhanced antitumor activity in vitro and in vivo. CONCLUSION: The results demonstrated that Tf-PTX-DNA-NLC can achieve impressive antitumor activity and gene transfection efficiency. Tf decoration also enhanced the active targeting ability of the carriers to NCl-H460 cells. The novel drug and gene delivery system offers a promising strategy for the treatment of lung cancer.